Development of high performance Fluoridated Hydroxyapatite coatings for biological applications - Wang, Yongsheng (2008)
This study indicates that incorporation of fluorine ions into HA lattice structure can benefit both the mechanical properties and in vitro biological properties of the coatings: with the incorporation of fluorine ions, the residual stress is significant reduced, while the adhesion properties and toughness are remarkably enhanced; the lowest solubility and the most positive stimulating effect (testing in acellular solutions and osteoblastic cell responses) are observed at a fluoridation degree of ~0.8-1.1, at which the coating takes the chemical formulation of Ca10(PO4)6(OH)1.2-0.9F0.8-1.1.